Genome-Wide Analysis of the Homeobox Gene Family and Identification of Drought-Responsive Members in Populus trichocarpa - Jing Hou (MDPI AG, 2021)
Homeobox (HB) genes play critical roles in the regulation of plant morphogenesis, growth and development. Here, we identified a total of 156 PtrHB genes from the Populus trichocarpa genome. According to the topologies and taxonomy of the phylogenetic tree constructed by Arabidopsis thaliana HB members, all PtrHB proteins were divided into six subgroups, namely HD-ZIP, ZF-HD, HB-PHD, TALE, WOX and HB-OTHERS. Multiple alignments of conserved homeodomains (HDs) revealed the conserved loci of each subgroup, while gene structure analysis showed similar exon–intron gene structures, and motif analysis indicated the similarity of motif number and pattern in the same subgroup. Promoter analysis indicated that the promoters of PtrHB genes contain a series of cis-acting regulatory elements involved in responding to various abiotic stresses, indicating that PtrHBs had potential functions in these processes. Collinearity analysis revealed that there are 96 pairs of 127 PtrHB genes mainly distributing on Chromosomes 1, 2, and 5. We analyzed the spatio-temporal expression patterns of PtrHB genes, and the virus-induced gene silencing (VIGS) of PtrHB3 gene resulted in the compromised tolerance of poplar seedlings to mannitol treatment. The bioinformatics on PtrHB family and preliminary exploration of drought-responsive genes can provide support for further study of the family in woody plants, especially in drought-related biological processes. It also provides a direction for developing new varieties of poplar with drought resistance. Overall, our results provided significant information for further functional analysis of PtrHB genes in poplar and demonstrated that PtrHB3 is a dominant gene regulating tolerance to water stress treatment in poplar seedlings.